PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PEMBELAJARAN KOOPERATIF BERBASIS MULTIPLE INTELLIGENCE DI KELAS VIII SMP BUDISATRYA MEDAN - Suwanto Suwanto (Universitas Islam Sumatera Utara, 2017)
The Problem in this research is lower capability of problem solving mathematical of students is the result of expository learning who did not considering multiple intelligences (multiple intelligence). The Purpose of this research was aimed to the improvement of mathematical problem solving capability and the interaction of KAM and learning factor toward the improvement problem solving capability. The type of this research is quasi-experiment research, subject of this research is VIII grade SMP Budisatrya Medan and sample selected by purposive sampling method. The subject of this research is divided into 2 class, first class is given cooperative learning based on multiple intelligence and the second class that given regular learning or expository learning. To measure the student’s capability that use the instrument that has been validated by 8 expert and already tested that showed the results of reliability question (0,946) for KAM and (0,905) for problem solving capability test. Data analysis was performed with ANOVA two lanes factorial. Based on the research results can be concluded that an increase in the ability of students' mathematical problem solving through cooperative learning based on multiple intelligence higher that regular learning and there is no interaction between prior knowledge of mathematics to increase the ability of solving problem mathematical.